2014
DOI: 10.3892/mmr.2014.2537
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced immune response against G250, induced by a heterologous DNA prime-protein boost vaccination, using polyethyleneimine as a DNA vaccine adjuvant

Abstract: Abstract. The heterologous DNA prime-protein boost vaccination approach has been widely applied as an immune treatment for carcinoma. However, inefficient delivery of DNA remains a major issue. In the present study, polyethyleneimine (PEI) was used as a DNA vector carrier to improve the transfection efficiency of the DNA vaccine and stimulate the humoral and cellular immunity against the renal carcinoma-associated antigen G250. A protein vaccine was included in the immunization strategy in order to produce a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“… 23 , 24 Studies have reported that various vaccines based on CAIX antigen can effectively stimulate antigen-specific immune responses and inhibit the growth of renal cancer. 25 , 26 The preliminary results of our research group also confirm that CAIX vaccine with the help of the adjuvant can induce antigen-specific multi-functional CD8 T cell immune response and suppress the tumor growth of renal cancer. 27 These results indicate that the developed DNA vaccine based on CAIX antigen is an effective way to treat renal cancer.…”
Section: Introductionsupporting
confidence: 63%
“… 23 , 24 Studies have reported that various vaccines based on CAIX antigen can effectively stimulate antigen-specific immune responses and inhibit the growth of renal cancer. 25 , 26 The preliminary results of our research group also confirm that CAIX vaccine with the help of the adjuvant can induce antigen-specific multi-functional CD8 T cell immune response and suppress the tumor growth of renal cancer. 27 These results indicate that the developed DNA vaccine based on CAIX antigen is an effective way to treat renal cancer.…”
Section: Introductionsupporting
confidence: 63%
“…Different types of PEI, antigens, constructed strategies and immune routes are chosen in constructing the PEI-based vaccines in vivo. Frequently researched diseases include AIDS, 24,[73][74][75][76] Listeria monocytogenes infection, 56,77 respiratory diseases, 54,78-80 B cell lymphoma, 38 herpes simplex virus attacks, 81 viral B hepatitis, 82 renal cell carcinoma, 83 melanoma 84 and others. 85 The PEI-based vaccines work through almost all the known immune routes, and usually mimic the pathogenesis of the diseases themselves.…”
Section: Progress Of In Vivo Applications Of Pei-based Vaccinesmentioning
confidence: 99%
“…Human renal carcinoma-specific antigen CAIX, composed of 459 amino acids, in which 38-414 amino acids constitute extracellular domain, was highly expressed in 90% of renal carcinoma tissues. CAIX expression was almost not detected in normal renal tissues or other normal tissues, and only a small amount of CAIX expression was detected in gastric mucosa and bile duct epithelial cells (12). CAIX shows apparent tumor specificity and could serve as an ideal target for immunotherapy of renal carcinoma (13).…”
Section: Introductionmentioning
confidence: 99%